1987
DOI: 10.1128/jvi.61.3.673-682.1987
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A 12S protein induces DNA synthesis and proliferation in primary epithelial cells in both the presence and absence of serum

Abstract: Infection of primary baby rat kidney (BRK) cells with an adenovirus that carries an ElA 12S cDNA in place of the normal ElA region (adenovirus 5 [Ad5] 12S) resulted in the induction of cellular DNA synthesis and proliferation of the epithelial cells in the population, even in the absence of serum. Increased cellular DNA synthesis was first detectable by 12 h after infection and was maintained at a 10-to 20-fold higher level than in mock-infected cells. By 5 days after infection there was a 10-fold-greater numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…This labeled RNA is then hybridized to excess DNA bound to nitrocellulose filters. The following DNA clones were used as probes on filters: ElA 5', 0 to 1,338 nucleotides; ElA 3', 1,338 to 1,538 nucleotides; E1B 5', 2,058 to 2,486 nucleotides; E1B 3', 3,328 to 3,786 nucleotides; E2A, 22,179 to 22,435 nucleotides; E4, 32,264 to 35,937 nucleotides; chicken P-actin (16); and mouse IGN heavy chain gene, -2,000 to + 1,700 nucleotides relative to the transcriptional start site (49).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This labeled RNA is then hybridized to excess DNA bound to nitrocellulose filters. The following DNA clones were used as probes on filters: ElA 5', 0 to 1,338 nucleotides; ElA 3', 1,338 to 1,538 nucleotides; E1B 5', 2,058 to 2,486 nucleotides; E1B 3', 3,328 to 3,786 nucleotides; E2A, 22,179 to 22,435 nucleotides; E4, 32,264 to 35,937 nucleotides; chicken P-actin (16); and mouse IGN heavy chain gene, -2,000 to + 1,700 nucleotides relative to the transcriptional start site (49).…”
Section: Methodsmentioning
confidence: 99%
“…By using a variety of genetic approaches it has been demonstrated that the 289R protein is necessary for modulating the rate of transcription from several viral early promoters (9, 13, 31, 45, 50) and some cellular genes (21,54), probably through its modification of some preexisting or induced cellular transcription factors (35,67). It has been suggested that both ElA proteins share domains which may suppress the expression of viral and cellular enhancer-dependent promoters (11,28,52,59) and that both proteins are necessary for the induction of cellular DNA synthesis and cell proliferation (33,38,49,53). Both proteins are required to establish and maintain the transformed cell phenotype by using primary or continuous cultures of rodent cells (25,30,32,40,43,51,69).…”
mentioning
confidence: 99%
“…In attempt to institute this strategy, gene transfer techniques were used to mediate the introduction of an oncogene and expression of its immortalizing protein product in primary SCN cells, because this method has yielded many useful cell lines with stable growth characteristics and parental phenotypic properties (Cepko, 1988(Cepko, , 1989(Cepko, , 1990. The capacity of the adenoviral early-region 1A (E1A) gene to immortalize progenitors of the rat SCN was explored in the present experiments because the 12S protein product of this oncogene induces DNA syn-thesis and extends the growth potential of primary cells derived from a variety of rat tissues (Quinlan and Grodzicker, 1987;Cone et al, 1988;Ryder et al, 1990;Seigel, 1996). The results reported here indicate that transfer of the 12S E1A gene into primary SCN cells in culture using retroviral vector constructed by Cone and coworkers (1988) yields growth-stimulated cell lines that express glial as well as neuronal phenotypes.…”
mentioning
confidence: 99%
“…E1A interacts with a number of cellular proteins important in regulating cell growth (8,29,49). They function predominantly as transcriptional adapters or are integral components of the transcriptional machinery, regulating transcription from both viral early and cellular promoters (11,37).…”
mentioning
confidence: 99%